Synchronous double primary malignancies of the pancreatic body and extrahepatic bile duct treated with pancreatoduodenectomy and splenic artery resection following neoadjuvant chemotherapy with gemcitabine plus nab-paclitaxel: a case report - Takahiro Murokawa; Takehiro Okabayashi; Kenta Sui; Motoyasu Tabuchi; Jun Iwata (Surgical Case Reports)
Abstract Background Primary pancreatic cancer with synchronous primary tumors in other organs is a rare condition, and its treatment largely depends on the progression of pancreatic cancer. Here, we describe a rare case of double primary malignancies involving borderline resectable pancreatic body and extrahepatic bile duct cancers that were successfully resected after neoadjuvant chemotherapy (NAC), subsequently avoiding total pancreatectomy. Case presentation A 61-year-old Japanese male was referred to our hospital by his general practitioner after presenting with elevated liver enzymes during a routine check-up for type 2 diabetes mellitus. He was diagnosed with synchronous borderline resectable pancreatic cancer in the body of the pancreas and lower extrahepatic bile duct cancer with obstructive jaundice. Abdominal computed tomography (CT) confirmed a hypovascular mass in the pancreatic body with partial encasement of the common hepatic artery, left gastric artery, celiac artery, and splenic artery and invasion of the splenic vein. Endoscopic retrograde cholangiopancreatography and bile duct biopsy confirmed lower bile duct cancer. Following multidisciplinary discussion, endoscopic retrograde biliary drainage was performed, and neoadjuvant chemotherapy comprising gemcitabine plus nanoparticle albumin-bound paclitaxel (GEM + nab-PTX) was administered. After a total of seven cycles of chemotherapy, follow-up CT showed that the size of the pancreatic lesion reduced, following which the patient underwent pancreatoduodenectomy with splenic artery resection. The postoperative course was uneventful without any surgical complications or intensive hypoglycemic treatment. The pathological diagnosis was pancreatic ductal adenocarcinoma (ypT3N1aM0 ypStage IIB/UICC 8th) with synchronous extrahepatic cholangiocarcinoma (ypT2N1M0 ypStage IIB/UICC 8th). R0 pancreatic resection was performed with an Evans grade III response to neoadjuvant chemotherapy. The patient was followed up and had no tumor recurrence at 22 months after surgery with adjuvant S-1 chemotherapy, however, died after 32 months after surgery due to multiple liver metastasis and para-aortic lymph node metastasis despite salvage GEM + nab-PTX chemotherapy. Conclusion In our case, neoadjuvant chemotherapy for borderline resectable pancreatic cancer and function-preserving pancreatoduodenectomy (R0 resection) for double primary malignancies achieved balanced patient survival and postoperative quality of life.